2015
DOI: 10.14198/jhse.2015.10.proc1.12
|View full text |Cite
|
Sign up to set email alerts
|

Sprint cycling performance and asymmetry

Abstract: Rannama, I., Port, K., Bazanov, B., & Pedak, K. (2015). Sprint cycling performance and asymmetry. J. Hum. Sport Exerc., 9(Proc1), pp.S247-S258. The purpose of this study was to examine the asymmetries in cyclist's lower limbs strength and in the pedalling kinematics during a seated sprinting test and to identify the relationships between asymmetries and maximal cycling power. 16 competitive road cyclists (20.6±3.7 yrs., 181.5±5.0 cm, 74.8±7.0 kg) performed 10 Sec isokinetic maximum power test with cadence 120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 36 publications
0
22
0
2
Order By: Relevance
“…The stronger limb in the accurate group was the stance limb, which may indicate that a more stable athlete is able to perform unilateral, technical tasks to a higher standard, although further research is warranted to fully corroborate this theory. Furthermore, in a group of competitive cyclists, peak torque asymmetries of the knee extensors (at 180°•sec -1 ) were negatively correlated (r = -0.50; p < 0.05) with power output during a 5-second maximal effort cycling test (Rannama et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The stronger limb in the accurate group was the stance limb, which may indicate that a more stable athlete is able to perform unilateral, technical tasks to a higher standard, although further research is warranted to fully corroborate this theory. Furthermore, in a group of competitive cyclists, peak torque asymmetries of the knee extensors (at 180°•sec -1 ) were negatively correlated (r = -0.50; p < 0.05) with power output during a 5-second maximal effort cycling test (Rannama et al, 2015).…”
Section: Discussionmentioning
confidence: 88%
“…The presence of heightened inter-limb asymmetries would be expected in sporting actions where preferred limb dominance is evident (Schiltz et al, 2009); although limited data are available to support this notion (Hart et al, 2016). Furthermore, inter-limb asymmetries for kinetic and kinematic variables may show different values; thus, not all observed side to side differences may be relevant to the performance outcome (Exell et al, 2016;Rannama et al, 2015). By more clearly understanding the effects of inter-limb asymmetries on physical and sports performance, it will provide practitioners with important information for the design of targeted testing and training strategies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review examining the effects of between-limb differences on physical and sporting performance demonstrated equivocal findings [8]. In summary, larger lower limb asymmetries in strength may be indicative of reduced jumping ability and power output [1,22]; however, when these differences are quantified during jumping tasks, their effect on locomotive activities appears inconclusive [13,16,18]. From an injury perspective, older literature has suggested that an asymmetry threshold of > 15% marks the point of heightened risk [3,20].…”
Section: Introductionmentioning
confidence: 99%
“…Inter-limb asymmetries have been defined as the force of contraction of two limbs being unequal (26). Research has highlighted associations between asymmetries in strength and a reduction in both kicking accuracy (19) and power output during cycling (35).…”
Section: Introductionmentioning
confidence: 99%